Assessment of Mitral Annular and Velocity Vector Imaging in Acute Myopericarditis. Issue 8 (1st July 2013) - Lynch, Matthew; O'Donnell, Robert; Weintraub, Neal L.; López‐Candales, Angel
Mini‐Abstract A 25‐year‐old student presenting with pleuritic chest pain, elevated troponin levels and subtle electrocardiogram abnormalities was treated for presumptive myopericarditis. On echocardiography, a lower than expected mitral annular displacement and systolic velocity were identified along with abnormalities in left ventricular strain generation that matched areas of edema and necrosis by cardiac magnetic resonance imaging. The patient was treated with NSAIDs and colchicine, and both the symptoms and echocardiographic abnormalities rapidly resolved. These novel findings suggest that changes in mitral annular displacement and systolic velocity occur in acute myopericarditis and may be useful in following the course of the disease.